Development of microanalytical methods for solving sample limiting biological analysis problems - Metto, Eve C. (Kansas State University, 2013)
Analytical separations form the bulk of experiments in both research and industry. The choice of separation technique is governed by the characteristics of the analyte and purpose of separation. Miniaturization of chromatographic techniques enables the separation and purification of small volume samples that are often in limited supply. Capillary electrophoresis and immunoaffinity chromatography are examples of techniques that can be easily miniaturized with minimum loss in separation efficiency. These techniques were used in the experiments presented in this dissertation. Chapter 1 discusses the underlying principles of capillary electrophoresis and immunoaffinity chromatography. In the second chapter, the results from immunoaffinity chromatography experiments that utilized antibody-coated magnetic beads to purify serine proteases and serine protease inhibitors (serpins) from A. gambiae hemolymph are presented and discussed. Serine proteases and serpins play a key role in the insect innate immunity system. Serpins regulate the activity of serine proteases by forming irreversible complexes with the proteases. To identify the proteases that couple to these serpins, protein A magnetic beads were coated with SRPN2 antibody and then incubated with A. gambiae hemolymph. The antibody isolated both the free SRPN2 and the SRPN2-protease complex. The purified proteases were identified by ESI-MS from as few as 25 insects. In Chapter 3, an integrated glass/PDMS hybrid microfluidic device was utilized for the transportation and lysis of cells at a high throughput. Jurkat cells were labeled with 6-CFDA (an internal standard) and DAF-FM (a NO specific fluorophore). Laser-induced fluorescence (LIF) detection was utilized to detect nitric oxide (NO) from single Jurkat cells. The resulting electropherograms were used to study the variation in NO production following stimulation with lipopolysaccharide (LPS). 3 h LPS-stimulation resulted in a two fold increase in NO production in both bulk and single cell analysis. A comparison of bulk and single cell NO measurements were performed and the average NO production in single cells compared well to the increase measured at the bulk cell level. Chapter 4 discusses the preliminary experiments with a T-shaped microfluidic device that exploit the property of poly(dimethylsiloxane) (PDMS) as an electroactive polymer (EAP), to enhance fluid mixing. EAPs deform when placed in an electric field. A thin layer of PDMS was sandwiched between chrome electrodes, positioned on the horizontal arms of the T design, and the electrolyte-filled fluidic channel. A potential difference across the PDMS layer caused it to shrink and stretch, thereby increasing the channel volume. The electrodes were actuated at 180[degrees] out of phase and this caused the fluid stream in the vertical channel to fold and stretch resulting in enhanced contact surface area and shorter diffusion distances of the fluid, thereby improving mixing efficiency. All the experiments presented in this dissertation demonstrate the application of miniaturized chromatographic techniques for the efficient analysis of small volume biological samples.
Keywords: Microfluidics; Immunoaffinity chromatography; Single cell analysis; Micromixing; Nitric oxide; Serpins; Chemistry (0485)